2022
DOI: 10.1038/s41467-022-28720-y
|View full text |Cite
|
Sign up to set email alerts
|

White matter integrity in mice requires continuous myelin synthesis at the inner tongue

Abstract: Myelin, the electrically insulating sheath on axons, undergoes dynamic changes over time. However, it is composed of proteins with long lifetimes. This raises the question how such a stable structure is renewed. Here, we study the integrity of myelinated tracts after experimentally preventing the formation of new myelin in the CNS of adult mice, using an inducible Mbp null allele. Oligodendrocytes survive recombination, continue to express myelin genes, but they fail to maintain compacted myelin sheaths. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 96 publications
2
44
0
Order By: Relevance
“…Does VAMP2/3-mediated exocytosis contribute to myelin maintenance? Recent studies report the breakdown of myelin sheaths upon inducing the genetic ablation of PLP1 or MBP during adulthood, suggesting that continuous transport of new material is necessary for myelin maintenance 70 , 71 . Single-cell transcriptomics of adult and aged mice revealed that VAMP2 and VAMP3 continue to be the highest expressed v-SNAREs in oligodendrocytes through the lifetime of a mouse 72 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Does VAMP2/3-mediated exocytosis contribute to myelin maintenance? Recent studies report the breakdown of myelin sheaths upon inducing the genetic ablation of PLP1 or MBP during adulthood, suggesting that continuous transport of new material is necessary for myelin maintenance 70 , 71 . Single-cell transcriptomics of adult and aged mice revealed that VAMP2 and VAMP3 continue to be the highest expressed v-SNAREs in oligodendrocytes through the lifetime of a mouse 72 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ab137043, RRID:AB_2749817), Iba1 (Wako, catalog no. 019-19741; RRID:AB_839504), myelin basic protein ( 88 ), MCT1 ( 54 ), NeuN (Chemicon, catalog no. MAB377B, RRID:AB_177621; Millipore, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is supported by the fact that at least two major myelin proteins (PLP and MBP) are shown to interact with autophagosomes, leading to the idea that CNS myelin itself could use this machinery for its degradation. Myelin synthesized during development is continuously exchanged and renewed, through a procedure named myelin turnover, by which new membranes replace old membranes, which then must be removed [ 7 , 63 ]. Our existing knowledge documents that the elimination of aberrantly deposited myelin -in case of trauma or during development as in myelin turnover- is accomplished through phagocytosis via microglia as well as endocytosis via astrocytes [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%